ANALISIS EKUITAS MEREK PRODUK WATERBASED FINISING IZYKOTE (KASUS DI KABUPATEN GIANYAR) - Adianti Adianti; I Putu Gde Sukaatmadja; Abdullah Jawas (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2012)
The purpose of this research are to recognize the brand awareness, brand trust, brand satisfaction, brand loyalty, and brand equity from Izykotewaterbased finishing product so we can arrange promotion strategy for the future. To carry on the purpose of those research, the research has been conducted toward for 160 respondent that taken from Kabupaten Gianyar. This research is using Purposive Sampling method by choosing a better respondent to become research sampling. The data was collected by questioner list. The analysis data did by Structural Equation Modeling (SEM), and the data were processed by AMOS verse 6, and SPSS verse 15. The result of this research shows, that the brand awareness factors having positive and significant influence to the brand trust for 0.47, the brand awareness have positive influence to the brandsatisfaction for 0.42, the brand trust have positive influence to the brand loyalty for 0.30, the brand satisfaction have a positive influence to the brand loyalty for 0.40, and the variable having a directly effect on positive and significant to brand equity is customer loyalty that is 0.32. The implication of the research result are to expected the improve and increase of the working performance manager especially marketing department to takes opportunities, necessary target market, carrying handicraft worker loyalty, that can be create to brand equity. Beside that company need to keep in touch with every worker who have basic to believe or trust, having satisfaction, and loyalty to used  Izykotewaterbased finishing, that make Izykotemore stronger brand at Kabupaten Gianyar